A Review of Virtual Reality Tools for Education: Applications, Databases and Future Directions - Augusto Ribeiro, David; Okwudili Matthew, Ugochukwu (INFOCOMP Journal of Computer Science, 2025)
Virtual Reality (VR) has emerged as a transformative technology in education, enabling immersive and interactive learning experiences that enhance student engagement and knowledge retention. This paper provides a comprehensive review of VR tools applied in educational settings, analyzing their functionalities, benefits, and challenges. Drawing parallels with energy-efficient algorithms like the Minimum Power Consumption Routing (MPCR) algorithm for IoT networks, this study explores how VR optimizes learning efficiency through dynamic and personalized environments. We discuss key VR platforms, relevant educational databases, and their applications in fields such as science, medicine, history, and vocational training. Additionally, we evaluate the performance of VR tools based on metrics such as student engagement, learning outcomes, and accessibility. The results indicate that VR tools significantly improve educational outcomes, though challenges like cost and technical complexity remain. Future directions include integrating VR with AI and expanding open-access databases to support broader adoption.